A Review of Kinect Computing Research in Education and Rehabilitation - Reisi Dehkordi, Sara; Ismail, Marina; Mat Diah, Norizan (International Journal of Engineering and Technology, 2018)
Recently Kinect technology device and its benefit in treatment approach are rapidly growing domain of interestingness for researchers and educators. For years, the games and applications, except their entertaining aspect, have discovered an educational and rehabilitation character. In recent years, gesture-based devices have evolved and attracted the attention of researchers, and thus to Microsoft Kinect Xbox. Already, many institutions worldwide use the Kinect to the learning or rehabilitation process. This paper indicates a review of articles to provide a preliminary reconsideration on Microsoftâ€™s Kinect for the Xbox 360. The 16 researches were reviewed in this study are in the filed of education or rehabilitation implemented to users with special needs. The distribution and reviews in the study were research methods, domain of research, learning content, and intended settings of the kinect system. The outcome of this study is the possible uses and limitations of kinect for education and rehabilitation.Â Â